Integrated farming system for sustainable livelihood, family food and nutritional security of Uttarakhand farmers - A case study - Kushwaha, Archana; Gupta, Vipul; Nayak, Harapriya; Singh, Vijay Kumar; Sharma, S. K.; Kushwaha, Arun; Kumar, Anil (Journal of the Inland Fisheries Society of India, 2021)
In the present investigation, integrated farming system (IFS) adopted by a progressive farmer in 1.0 ha area, in village Chalthi, situated in Champawat district of Uttarakhand was analyzed as a model for its economics, benefit to cost ratio and extent to overcome food and nutritional security. The main components of IFS were fish, dairy, poultry, vegetables, orchard, bee keeping and mushroom production. A total of Rs. 6,94,000.00 was earned with B:C ratio of 3.08 from this IFS model. The composite fish farming of common carp, silver carp and grass carp was undertaken in a fish pond and 40 kg of fish was harvested over a period of 6-8 months realizing net income of Rs.5800.00. The pond dyke and adjacent fields were used for cultivation of aerial vegetables, fruit trees (mango, litchi, lemon, plum, guava and mulberry) and fodder crops (maize and oats). Two cows (breed Gir) and 200 No. poultry birds (breed Kadaknath, RIR, Guinea fowl, Uttra fowl) were included in the IFS. Pink oyster mushroom (Pleurotus djamor) was also promoted as a component of IFS for income generation. The mushroom yield was 2.28 quintals accounting gross income of Rs.1,82,400.00. Bee keeping (Indian honey bee Apis cerana indica) also made contribution of Rs. 2,00,000.00 over a period of 6 months from 80 boxes. Poultry (Rs 1,20,000.00), fruit crops (Rs 1,00,000.00) and vegetables productionÂ (Rs 18,000) also contributed significantly to the gross income in present IFS. The farmer reported that he did not buy any food commodity from outside for 8 months in a year except rice and wheat flour. As a result, it can be argued that IFS has been found to be most profitable and suitable enterprise for hill farmers to achieve sustainable livelihood, family food and nutritional security.Key words Integrated farming system; Food security; Nutrition security; Fish; Mushroom; Poultry